Synthesis of tetrasubstituted pyrazoles containing pyridinyl substituents - Jansa, Josef; Schmidt, Ramona; Mamuye, Ashenafi Damtew; Castoldi, Laura; Roller, Alexander; Pace, Vittorio; Holzer, Wolfgang (Beilstein Journal of Organic Chemistry, 2017)
A synthesis of tetrasubstituted pyrazoles containing two, three or four pyridinyl substituents is described. Hence, the reaction of 1,3-dipyridinyl-1,3-propanediones with 2-hydrazinopyridine or phenylhydrazine, respectively, affords the corresponding 1,3,5-trisubstituted pyrazoles. Iodination at the 4-position of the pyrazole nucleus by treatment with I2/HIO3 gives the appropriate 4-iodopyrazoles which served as starting materials for different cross-coupling reactions. Finally, Negishi cross-coupling employing organozinc halides and Pd catalysts turned out to be the method of choice to obtain the desired tetrasubstituted pyrazoles. The formation of different unexpected reaction products is described. Detailed NMR spectroscopic investigations (1H, 13C, 15N) were undertaken with all products prepared. Moreover, the structure of a condensation product was confirmed by crystal structure analysis.
Keywords: Negishi coupling; NMR (1H; 13C; 15N); pyrazole; pyridine; X-ray structure analysis